JWH-210 (4-etil-1-naftalenil)(1-pentil-1h-indol-3-il)-metanon ve metabolitinin (jwh-210-n-5-karboksi pentil) lc-ms/ ms ile kanda tayini - Ersoy, Canan (My University, 2017)
Ülkemizde sıklıkla Bonzai/ Jamaika olarak, yurtdışında ise K2/ Spice olarak adlandırılan psikoaktif maddeler sentetik kannabinoidlerdir. ABSTRACT Psychoactive herbal mixtures generally known as Bonzai / Jamaika in Turkey and K2/ Spice in abroad that contains synthetic cannabinoids.
Keywords: Blood; JWH-210; JWH-210-N-(5-carboxypentyl); JWH-210-N-(5-karboksi pentil); kan; Kimya; Kimya, Analitik; LC-MS/ MS. Synthetic cannabinoids; LC/ MS/ MS; Sentetik kannabinoid; Uyuşturucu maddeler